Effects of Reflexology Therapy Implementation for Postpartum Mothers’ Well-being at a Health Care Facility - Mudy Oktiningrum; Tia Nurhanifah; Mianti Nurizky (Jurnal Bidan Cerdas, 2026)
Background: The well-being of postpartum mothers is a crucial aspect of maternal health services. However, many women encounter challenges during childbirth, including severe pain, stress, and a lack of information on pain management. Data from the Association of Indonesian Hospitals show that 15% of postpartum mothers experience complications, 21% suffer from severe pain, and 64% do not receive information on how to reduce labor pain. Reflexology therapy serves as a non-pharmacological method to relieve pain and enhance relaxation. This study analyzed the effectiveness of reflexology therapy in reducing pain and stress while improving the satisfaction of postpartum mothers with maternal health services. Methods: The study used a quasi-experimental design with a pretest–posttest control group, conducted from June to October 2025 at Gondo Suwarno Hospital, Ungaran. Researchers purposively selected 60 postpartum mothers and divided them into two groups: an intervention group and a control group. Data were analyzed using paired t-tests and independent t-tests with a significance level of 0.05. Results: Reflexology therapy significantly reduced pain and stress scores and increased maternal satisfaction in the intervention group, while no significant changes were observed in the control group. Between-group comparisons confirmed that the magnitude and direction of outcome changes favored the intervention group (p < 0.05). Reflexology therapy significantly reduced pain and stress levels in the intervention group compared to the control group (p < 0.05) and increased satisfaction with health services. Conclusion: Reflexology therapy contributes to postpartum maternal well-being through physiological pain modulation, psychological relaxation, and improved perceptions of care quality. Healthcare providers are encouraged to integrate reflexology as a complementary intervention in maternal health services.